Peritoneal Involvement Is More Common Than Nodal Involvement in Patients With High-Grade Appendix Tumors Who Are Undergoing Prophylactic Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy. Issue 11 (November 2017) - Mehta, Akash; Mittal, Rohin; Chandrakumaran, Kandiah; Carr, Norman; Dayal, Sanjeev; Mohamed, Faheez; Moran, Brendan; Cecil, Tom
Abstract : BACKGROUND: Right hemicolectomy is routinely recommended in patients with histologic findings of high-grade appendix tumors after appendicectomy. Undetected peritoneal disease may be encountered at surgery. In high-grade appendix tumors with disease detected radiologically, complete cytoreduction may not be possible and outcomes poor. For these reasons, we adopted a policy of prophylactic cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. OBJECTIVE: The purpose of this study was to quantify the rates of peritoneal and nodal metastatic disease in patients with high-grade appendix tumors without obvious metastatic disease and to report the long-term outcomes of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in these patients. DESIGN: Data regarding peritoneal and nodal metastatic disease were extracted from surgical and histologic records. SETTINGS: The study was conducted at a high-volume tertiary referral center for peritoneal malignancy. PATIENTS: Patients referred with histologically high-grade appendix tumors at appendicectomy, without detectable metastatic spread, between January 1994 and September 2016 were included MAIN OUTCOME MEASURES: A total of 62 patients with high-grade pathology at appendicectomy, without clinical or radiological peritoneal disease, underwent complete cytoreduction with hyperthermic intraperitoneal chemotherapy. RESULTS: Thirty-five (57%) of 62 patients had peritoneal disease (median peritoneal cancer index 5 (range, 1–28)). Eleven (31%) of 35 had microscopic peritoneal disease. Overall, 23 (37%) of 62 had peritoneal disease beyond the confines of a standard right hemicolectomy. Nine (15%) of 62 had nodal involvement. Mean overall and disease-free survival were 110.9 (95% CI, 94.8–127.0 mo) and 102.1 months (95% CI, 84.3–119.9 mo), with 5-year overall and disease-free survival of 83.2% and 76.0%. LIMITATIONS: The retrospective nature limits the interpretation of these results. CONCLUSIONS: Complete cytoreduction was achieved in all of the patients, with excellent long-term survival. The incidence of peritoneal spread (57%) compared with nodal involvement (15%) supports cytoreductive surgery and hyperthermic intraperitoneal chemotherapy as definitive treatment rather than prophylaxis in patients with high-grade appendix tumors, even without radiologically detectable disease. High-grade appendix tumors benefit from early aggressive operative management to deal with potential peritoneal and nodal spread and should be considered for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. SeeVideo Abstract athttp://links.lww.com/DCR/A360 .